A Highly Active Chimeric Lysin with a Calcium-Enhanced Bactericidal Activity against Staphylococcus aureus In Vitro and In Vivo - Xiaohong Li; Shujuan Wang; Raphael Nyaruaba; Huan Liu; Hang Yang; Hongping Wei (MDPI AG, 2021)
Lysins, including chimeric lysins, have recently been explored as novel promising alternatives to failing antibiotics in treating multi-drug resistant (MDR) pathogens, including methicillin-resistant Staphylococcus aureus (MRSA). Herein, by fusing the CHAP (cysteine, histidine-dependent amidohydrolase/peptidase) catalytic domain from the Ply187 lysin with the non-SH3b cell-wall binding domain from the LysSA97 lysin, a new chimeric lysin ClyC was constructed with Ca2+-enhanced bactericidal activity against all S. aureus strains tested, including MRSA. Notably, treating S. aureus with 50 μg/mL of ClyC in the presence of 100 μM Ca2+ lead to a reduction of 9 Log10 (CFU/mL) in viable bacterial number, which was the first time to observe a lysin showing such a high activity. In addition, the effective concentration of ClyC could be decreased dramatically from 12 to 1 μg/mL by combination with 0.3 μg/mL of penicillin G. In a mouse model of S. aureus bacteremia, a single intraperitoneal administration of 0.1 mg/mouse of ClyC significantly improved the survival rates and reduced 2 Log10 (CFU/mL) of the bacterial burdens in the organs of the infected mice. ClyC was also found stable after lyophilization without cryoprotectants. Based on the above observations, ClyC could be a promising candidate against S. aureus infections.